Kemasan Plastik Garam Beriodium - Hamdani Machmud (Jurnal Kimia dan Kemasan, 1985)
The choice of a packaging material for a particular product raises a number of important considerations. Applications of polypropylene and polyethylene plastic container has widely used for iodized salt packaging in the form of bag has indicated that it was the most economic and practical container, for it's characteristic of the material is easy to form, light weight, variety of colour, flexible.From technical point of view the packaging's function are : (1) to keep the product in a good condition during distribution and storage. (2) to protect the product from contamination.